IDENTIFIKASI ALAT PENANGKAPAN IKAN DI KECAMATAN LEMBAH MASURAI KABUPATEN MERANGIN PROVINSI JAMBI - Nia Ramadani; Mohd. Yusuf Amrullah; Syafrialdi Syafrialdi; Muhammad Natsir Kholis (SEMAH Jurnal Pengelolaan Sumberdaya Perairan, 2022)
Lembah Masurai District is one of the sub-districts in Merangin Regency, which consists of 15 (fifteen) villages which are fed by the Siau River, Pangi River, Nilo River and other small rivers which empties into the Tembesi River.Identification of fishing gear can provide information on the fishing gear used by the community. In addition, these results can be used as a basis for researchers to develop identification of fishing gear in the waters, especially in the Masurai Valley. The method used in this study is a survey and observation method. The method used in this study is a survey and observation method. There are 2,164 fishing gears identified in the Lembah Masurai Subdistrict and classified into 5 (five) groups namely, 788 hook and lines units, 167 gill nets units, 213 falling gear units, 309 traps units, and 687 grappling and wounding units.